The influence of genotype and agroecological conditions on aminoacids composition of naked oats - sterba, Zdenek; Moudrý, Jan (MTT, 2004)
Czech Republic plays important role in both breeding and growing of naked oats. Their proteins have the highest biological value among the cereals proteins with favourable aminoacid composition and a high level of lysine. Main goal of this work was to evaluate influence of genotype and main agroecological conditions on aminoacids contents in naked oats grain. We observed two varieties (Abel, SGK-7555) on four control sites (Nechanice, Kujavy, Hradec nad Svitavou, Krukanice) from 1995 to 1997. The contents of aminoacids was determined by column chromatography. The contents of aminoacids was analogous to the figures reported by Moudrý & Èermák (1995) and Cuddeford (1990), except from the aminoacids glycine and alanine. Moudrý & Èermák (1995) detected approximately double contents of aminoacids glycine and alanine. On the contrary, lower contents of fenylalanine and histidine were found out. No other substantial differences were found. The rate of aminoacids contents in naked oats is mainly influenced by actual season conditions, locality and finally genotype. Statisticaly insignificant differences in aminoacids contents were detected between varieties in most amonoacids. Statisticaly significant differences in aminoacids contents were detected between locality and season conditions (temperature, precipitation. No significant negative correlation was found between the contents of N compounds and aminoacids contents including lysin. The lower contents of N substances does not automatically lead to worse aminoacids composition. Cuddeford, D. 1990. In: Oats and triticale a growing market. National Agricultural Conference, April, Stoneleigh; Moudrý, J. & Èermák, B. 1995. In Czech.
Keywords: Ka; naked oats; genotype; agroecological conditions; aminoacids